A new sponge-inhabiting leptostracan species of the genus Nebalia (Crustacea: Phyllocarida: Leptostraca) from the Veracruz Coral Reef System, Gulf of Mexico - Ortiz, Manuel; Winfield, Ignacio; Cházaro-Olvera, Sergio (Zootaxa, 2011)
A new species of Leptostraca, Nebalia villalobosi, is described from the Veracruz Coral Reef System, SW Gulf of Mexico. The new species was found associated with the sponge Ircinia fistularis (Demospongiae) from the Blanquilla reef at a depth of 12 m. It differs from the closely related species N. longicornis and N. lagartensis in the form of the eyes and rostrum, the number of articles in the antennular and antennal flagella, the inner border of article 3 on the mandible palp, the length of the exopod of maxilla 2, the rounded denticles on pleonite 6, the enlarged tip on pleopod 5, and the caudal furcae being slightly longer than the telson and pleonite 7 combined. This is the first record of a leptostracan associated with the sponge Ircinia fistularis.